Peran Minat Memediasi Pengaruh Quality Service Transaksi Digital terhadap Costumer Satisfaction Pengguna Layanan OVO - Asep Machpudin; Ade Titi Nifita; Garry Yuesa Rosyid; Ade Perdana Siregar (J-MAS (Jurnal Manajemen dan Sains), 2020)
The development of digital technology is increasing every year, various types of digital technology that exist today is a development of technology that has been there before. The presence of the digital age has helped to encourage human interest to transform digitally. The objectives in this study are: (1) Identifying the effect of digital transaction service quality on customer satisfaction of OVO users, (2) Identifying the effect of service quality of digital transactions on interests, (3) Identifying the effect of interest on customer satisfaction of OVO service users. (4) Identifying the role of interest is able to mediate the effect of digital transaction quality service on customer satisfaction of OVO service users. The population of this research is the people of Jambi City while the sample is the people of Jambi City who more than once used OVO services as many as 150 people. The data method uses path analysis. The results of the study note that quality service has a significant influence on OVO service user interest, quality service and interest have a significant influence on customer satisfaction on OVO service users and quality service has a significant influence on customer satisfaction of OVO service users through interest in Jambi City